TEKS GEGURITAN DALEM TARUKAN : ANALISIS STRUKTUR DAN NILAI - Cokorda Istri Agung, Suprabi (Humanis, 2015)
One of the most inspairing classic literature of Balinese culture is Geguritan. Geguritan contained of pupuh, every single pupuh bond of padalingsa. This script explore about Geguritan Dalem Tarukan which is has a very special “society core” on its structure, off course social value in Balinesse daily life. It teach us about Panca Sradha. Our five principles about credence of Ida Sang Hyang Widhi Wasa and Karma Phala. It also tell us about holy sacrifice called yadnya. And last but not least bring us into “satya”. Satya (faith) is a credence how we believe in Lord an environment. Satya will bring us to a very bright leading value as a leader in society. Geguritan Dalem Tarukan has a wonderful historical value for young Balinesse generations.
Keywords: Geguritan, Structure, Society core